Using the M68HC11 microcontrollers a guide to interfacing and programming the M68HC11 microcontroller - Skroder, John C. (Prentice Hall, 1997)
Useful for undergraduate courses in microprocessors and microcontrollers, this book deals with instrumentation and control, industrial electronics, fuzzy logic and inference, M68HC11 assembly language and machine code. Providing coverage of the M68HC11 microcontroller, it also includes memorizing facts and concepts.